2009
DOI: 10.4238/vol8-1gmr544
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory response to isocyanates and onset of genomic instability in cultured human lung fibroblasts

Abstract: ABSTRAcT. Lungs comprise the primary organ exposed to environmental toxic chemicals, resulting in diverse respiratory ailments and other disorders, including carcinogenesis. Carcinogenesis is a multi-stage phenomenon, which involves a series of genetic alterations that begin with genomic instability provoked by certain factors such as inflammation and DNA damage and end with the development of cancer. Isocyanates such as methyl isocyanate are the chief metabolic intermediates in many industrial settings with d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 38 publications
0
21
0
Order By: Relevance
“…Increased p53 activity in response to DNA damage blocks the proliferation of cells in the G1 phase of the cell cycle [48]. In line with this cellular phenomenon, authors' findings in IMR-90, FHC and B/CMBA.Ov cells treated with MIC showed significant cell cycle arrest both at early G1 and G2/M phases, eventually setting the stage for aneuploidy [25,26,47]. These results indicate imbalance in ploidy levels and are probably the response of check-point proteins and interruption of cell cycle progression, due to toxic MIC treatment.…”
Section: Cell Cycle Deregulationmentioning
confidence: 56%
See 2 more Smart Citations
“…Increased p53 activity in response to DNA damage blocks the proliferation of cells in the G1 phase of the cell cycle [48]. In line with this cellular phenomenon, authors' findings in IMR-90, FHC and B/CMBA.Ov cells treated with MIC showed significant cell cycle arrest both at early G1 and G2/M phases, eventually setting the stage for aneuploidy [25,26,47]. These results indicate imbalance in ploidy levels and are probably the response of check-point proteins and interruption of cell cycle progression, due to toxic MIC treatment.…”
Section: Cell Cycle Deregulationmentioning
confidence: 56%
“…Free radicals thus generated impact biochemical component of the cell, with lipids, proteins and nucleic acids being the most important targets. [25,26,34,35,44,46,47]. Our results imply that MIC treatment causes the formation of carcinogen-DNA adducts and induces alterations to DNA ultra-structure.…”
Section: Mitochondrial Retrograde Signalingmentioning
confidence: 57%
See 1 more Smart Citation
“…Recently, in our preceding study we had reported an enhanced production of inflammatory cytokines upon exposure of immune cells to isocyanates in vitro 28,29) . In addition, in-vitro MIC exposure to lung fibroblast cells was also observed to induce inflammatory response which further leads to genomic instability 30) . In present study, we observed a significant increase in the circulating levels of inflammatory cytokines in group III (MIC exposed group) in comparison to the control group I (control group within Bhopal) and group II (control group outside Bhopal) (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The cause and genesis of the accident, spectrum of health effects, constituents of the toxic gas cloud and their possible role in the causation of adverse effects are well-debated [7]. Thanks to cellular model systems, the molecular mechanisms underlying the toxico-genomic implications of MIC exposure have now been better understood [8][9][10][11][12]. However, it has been increasingly realized that the study of the human aspect of the tragedy had perhaps been neglected.…”
Section: Introductionmentioning
confidence: 99%